Energy Efficiency Analysis of 3D Printing Machines (Additive Manufacturing) in Supporting Local MSMEs: Poverty Alleviation Opportunities in the Digital Era - Anton Nugroho; Wawan Kusdiana (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid development of additive manufacturing, particularly 3D printing technology, has created new opportunities for small and medium enterprises (SMEs) to engage in flexible and low-volume production within the digital economy. Energy efficiency has become a critical factor influencing the operational feasibility of this technology, especially for SMEs that operate with limited financial resources and infrastructure. Understanding the energy performance of 3D printing machines is therefore essential for evaluating their potential role in supporting sustainable entrepreneurship and poverty alleviation. Purpose. This study aims to analyze the energy efficiency of 3D printing machines in additive manufacturing processes and examine their potential contribution to strengthening local SMEs and expanding economic opportunities in the digital era. Method. The research employs a quantitative experimental design combined with descriptive analysis. Energy consumption data were collected using digital power meters during standardized printing experiments involving several desktop 3D printers commonly used by SMEs. Statistical analysis was conducted to compare machine efficiency and evaluate the relationship between printing parameters and electricity consumption. Results. The findings indicate significant differences in energy consumption across machine types and printing configurations. Optimized parameter settings and efficient machine architecture reduce electricity usage and operational costs. Evidence from SME production contexts demonstrates that energy-efficient additive manufacturing supports faster prototyping and flexible small-scale production. Conclusion. Energy-efficient 3D printing technology represents a promising tool for strengthening SME productivity and fostering inclusive economic development in the digital era.